Value relevance of investment properties’ fair value and board characteristics in Malaysian Real Estate Investment Trusts - Mei, Zi Tan; Mohamat Sabri Hassan,; Zaini Embong, (Fakulti Ekonomi dan Pengurusan, 2014)
Prior studies in Malaysia indicate that fair value of investment properties are not value relevant in various industries. Unlike those industries, Malaysian Real Estate Investment Trusts (MREITs) is a capital-intensive industry where the investment properties made up the majority of the MREITs total assets. Furthermore this industry is subjected to stringent monitoring by the Securities Commission (SC) which requires MREITs to adopt the fair value model and revalue their investment properties for at least once in every three years. Therefore, results from previous studies cannot be generalized to this industry. Hence, this study investigates whether fair value on investment properties is value relevant in the MREIT industry. It also examines the effect of board characteristics on the share prices of MREITs. Secondary data was obtained from annual reports of twelve listed MREITs on Bursa Malaysia from 2006 to 2011 and analyzed using multiple regression analysis. The results indicate that the information on the fair value of investment properties (as presented in balance sheet) is significantly related to share price of MREITs. However, the changes in fair value (revaluation surplus), as presented in income statement is not significantly related to the share price. The findings suggest that only fair value of investment properties (FVIP) is useful for investors to make their investment decisions. This study also found a positive and significant association between board independence and share prices of MREITs. It indicates that independence of directors in MREIT firms is also important to investors that it is reflected in the share price. This study adds to the limited literature on MREITs. The results indicate that investors do value the fair value information provided by MREITs and support the fair value accounting in REITs. The findings of this study could be used by regulators in improving the future revaluation guidelines for the REIT industry.